Pengembangan Media Pembelajaran Berbasis Video Animasi pada Materi Organ Gerak Hewan di Kelas V Sekolah Dasar - Rahayu, Risca; Meliyani, Rika; Putri, Firda Aisyah (Indonesian Journal of Science, Technology, Engineering, Art, and Mathematics Education, 2024)
The problem of this research is the lack of interesting and effective learning methods for elementary school students, especially to understand the material of motion organs in animals. The purpose of the research is to develop animation-based learning videos using the Canva application to increase students' interest and subject knowledge. The method used in this research is Research and Development (R&D) with the ADDIE model which includes student needs analysis, media design, material development, implementation and evaluation. The animated video was tested by students for feedback before being widely used, to ensure its effectiveness in learning. The results showed that the animation-based learning video developed effectively increased the interest and knowledge of animal movement of grade 5 students. The trial with six students resulted in positive feedback on all aspects of material, media, and language. achieved a score of 100%, displaying a more interesting and fun lesson. The conclusion of this study is that the use of animated videos in teaching can increase students' interest and understanding. The implications of this study show that the use of animation-based learning media can improve students' engagement and comprehension in primary school. Teachers are advised to incorporate animated videos into their teaching methods to create a more engaging learning experience.